Ion Channel Function During Oocyte Maturation and Fertilization - Carvacho, Ingrid; Piesche, Matthias; Maier, Thorsten J.; Machaca, Khaled (Frontiers in Cell and Developmental Biology, 2018)
The proper maturation of both male and female gametes is essential for supporting fertilization and the early embryonic divisions. In the ovary, immature fully-grown oocytes that are arrested in prophase I of meiosis are not able to support fertilization. Acquiring fertilization competence requires resumption of meiosis which encompasses the remodeling of multiple signaling pathways and the reorganization of cellular organelles. Collectively, this differentiation endows the egg with the ability to activate at fertilization and to promote the egg-to-embryo transition. Oocyte maturation is associated with changes in the electrical properties of the plasma membrane and alterations in the function and distribution of ion channels. Therefore, variations on the pattern of expression, distribution and function of ion channels and transporters during oocyte maturation are fundamental to reproductive success. Ion channels and transporters are important in regulating membrane potential, but also in the case of calcium (Ca2+), they play a critical role in modulating intracellular signaling pathways. In the context of fertilization, Ca2+ has been shown to be the universal activator of development at fertilization, playing a central role in early events associated with egg activation and the egg-to-embryo transition. These early events include the block of polyspermy, the completion of meiosis and the transition to the embryonic mitotic divisions. In this review, we discuss the role of ion channels during oocyte maturation, fertilization and early embryonic development. We will describe how ion channel studies in Xenopus oocytes, an extensively studied model of oocyte maturation, translate into a greater understanding of the role of ion channels in mammalian oocyte physiology.